Development of an Online Multilingual Educational Programme for Parents of Dual-Career Athletes: A Participatory Design - Capranica, Laura; Guidotti, Flavia; Gonçalves, Carlos; Blondel, Laurence; Bovis, Matteo; Costa, Rute; Debois, Nadine; Figueiredo, Antonio; MacDonncha, Ciaran; Pecnikar-Oblak, Viktorija; Patoret, Jean-Luc; Pišl, Andrej; et al. (Frontiers in Psychology, 2022)
Abstract There is a need for educational support to empower parents in sustaining talented athletes pursuing aThere is a need for educational support structures to empower parents in sustaining talented athletes pursuing academic and sport careers (e.g., dual career). The present work describes the participatory design used to develop a series of educational resources and the subsequent iterations used to evaluate the content of the EMPATIA online education programme for parents of dual career athletes. Following an ethnographic approach, the project team (18 dual career experts) engaged in four iterations (i.e., rounds) planned to develop (round 1 and 2) educational material from preliminary evidence- (systematic literature review) and eminence- (focus groups and concept mapping) knowledge, and to evaluate the educational programme (round 3 and 4) engaging end users (n=76) and other stakeholders (9 dual career experts). The EMPATIA programme was developed and organized in four modules labelled after macro aspects parents could ask about dual career: “Why” (the definition and challenges of dual career for athletes and their parents), “What” (insights, guidelines, and suggestions on the parental role in support of student-athletes), “How” (practical advices on planning dual career at sport and academic levels, and post-sport careers), and “Where” (finding legal information or counselling on dual career). Despite positive evaluations of the programme were found, parents of dual career athletes attributed higher scores with respect to those of dual career experts. The participatory approach presented in this work enables developers to apply a systematic and multi-disciplinary approach towards the creation of educational programmes for parents. The cooperation between dual career researchers, experts from high performance centres, Olympic bodies, sport clubs, and parents of elite student-athletes of different sports and nationalities created an educational programme suitable for end users to support parenting athletes in combining their sports and academic careers.